The impact of socio-cultural, economic and governmental factors on entrepreneurship intentions. - Chang, Jean Kwee Lian. (2013)
The dearth of entrepreneurs in Singapore and the growing concern of the government towards this issue in recent years, have motivated the project group to look more in depth into entrepreneurial intentions in Singapore. Thereby, this paper aims to provide insight into the factors influencing the entrepreneurial environment in Singapore. More precisely, the study examines the impact of socio-cultural factors, economic and governmental factors on the feasibility, desirability and intention to create a new business venture in Singapore.